MODEL PEMBELAJARAN ILMU NAHWU MENGGUNAKAN KITAB AL-JURRUMIYAH : (Studi Analisis Deskriptif di Kelas VII Putri Pondok Pesantren Nurus Sunnah Kota Tegal) - Trias Widyaningrum; Taufiq Fauzan Ginanjar (CV. Lafadz Jaya, 2025)
This study aims to describe the model of Arabic grammar instruction using Al-Jurrumiyah with Qiyasiyah and Istiqraniyah approaches in the seventh-grade female class of Nurus Sunnah Islamic Boarding School, Tegal City. The background of this study is based on the importance of Arabic grammar mastery as a foundation for understanding Arabic texts in Islamic boarding schools, as well as the persistent difficulties faced by beginner students in comprehending and applying grammatical rules contextually. This research employed a qualitative approach with a descriptive qualitative design. Data were collected through classroom observations, interviews with teachers and students, and document analysis, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that Arabic grammar instruction using Al-Jurrumiyah applies the Qiyasiyah model by presenting grammatical rules at the beginning of the lesson followed by illustrative examples, while the Istiqraniyah model is implemented by introducing language examples prior to formulating grammatical rules. Both models are applied alternately according to the characteristics of the material and students’ abilities. Supporting factors include the systematic structure of the book and the active role of teachers, while inhibiting factors involve students’ varying initial competencies and limited instructional time. The study concludes that a balanced application of Qiyasiyah and Istiqraniyah models contributes positively to improving beginner students’ understanding of Arabic grammar.